2019
DOI: 10.1016/j.biocon.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Prairie wetlands confer consistent migrant refueling conditions across a gradient of agricultural land use intensities

Abstract: Increasing global demands for land to produce food, fiber, and energy threatens temperate grassland and wetland ecosystems, catalyzing a need to inform strategic and efficient approaches to conserve ecological function in these ecosystems. In the Prairie Pothole Region of North America, an extensive agricultural footprint has grown since the late 19th century and recently expanded in extent and intensity of cultivation in response to improved technology and global demands. Despite extensive modifications, many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 112 publications
2
17
1
Order By: Relevance
“…Chironomids and odonates could respond to factors that may covary with a DOC gradient such as whole-system productivity, vegetation community composition or sediment characteristics (Bortolotti et al, 2016;Euliss & Mushet, 1999). The negative associations between TP and chironomid and odonate abundances coupled with positive associations with the amount of surrounding cropland were surprising, although wetland invertebrate abundance was positively associated with cropland cover in a recent study (Janke, Anteau, & Stafford, 2019). Positive associations between cropland and invertebrates could be driven by the association that more productive land tends to have higher agricultural intensity.…”
Section: Aquatic Macroinvertebratesmentioning
confidence: 94%
See 1 more Smart Citation
“…Chironomids and odonates could respond to factors that may covary with a DOC gradient such as whole-system productivity, vegetation community composition or sediment characteristics (Bortolotti et al, 2016;Euliss & Mushet, 1999). The negative associations between TP and chironomid and odonate abundances coupled with positive associations with the amount of surrounding cropland were surprising, although wetland invertebrate abundance was positively associated with cropland cover in a recent study (Janke, Anteau, & Stafford, 2019). Positive associations between cropland and invertebrates could be driven by the association that more productive land tends to have higher agricultural intensity.…”
Section: Aquatic Macroinvertebratesmentioning
confidence: 94%
“…As natural grasslands are converted to farmland, bird specialists decline and some generalist species benefit (Julliard, Clavel, Devictor, Jiguet, & Couvet, 2006;Kampichler, Turnhout, Devictor, & Jeugd, 2012). In Alberta, aquatic and terrestrial omnivores, terrestrial invertivores and terrestrial carnivores showed a positive association with cropland, and breeding birds such as some duck species, Red-winged Blackbird, and Ring-billed Gull (aquatic and terrestrial omnivores) and Long-billed Curlew (terrestrial carnivore) can increase in response to increases in hayfields and croplands (Clark & Weatherhead, 1986;Janke et al, 2019;Jobin, DesGranges, & Boutin, 1996). Patterns could also be associated with higher soil fertility in cropland.…”
Section: Avian Species Richness and Functional Groupsmentioning
confidence: 99%
“…Spatial data on species of concern are missing or incomplete in many geographies and for many taxa. For example, seasonal or temporary wetlands have a high value for waterfowl, particularly in the Prairie Pothole Region, but can be difficult to map, especially when embedded in agricultural fields or other disturbed areas [194] and the distribution and migratory pathways of bats are not well known [87,195]. Therefore, as with all development projects, wildlife concerns should be addressed early in the site identification process, should be made in the context of landscape-level considerations, and should be fully explored before considering minimization and offset measures.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, farms located near riparian zones or wetlands tend to have higher concentrations of waterfowl, cranes, and waders that use the area to feed and roost (Pearse et al, 2013;Beatty et al, 2014;Bengtsson, 2016;Si et al, 2018). The presence of these habitats appears to allow riparian-dependent species to adequately replenish fat reserves regardless of the intensity of the surrounding agriculture (Janke et al, 2019). For many bird species, use of agricultural areas for stopovers may be due to edges, ecotones and surrounding habitat, and these birds' association with cropland may be secondary.…”
Section: Farm Managementmentioning
confidence: 99%